A Case Report on the Impact of a Lean Poly Cystic Ovarian Syndrome on Fertility and Potential Benefit of Ayurveda Regime (AYUSHDHARA, 2022)
Despite of advances in Artificial Reproductive Techniques (ART), female infertility is the predominant health issue faced by approximate 15% couples globally.Out of the ovarian factors responsible for infertility, PCOS is a burning issue worldwide affecting female fertility and creating endocrine level disturbances. Case presentation: We are reporting a case of primary infertility presenting with Lean phenotypical features and USG findings of PCOS. She underwent conventional Hormonal therapy for two years and single cycle of IVF which resulted in failure. On evaluating the parameters in view of Ayurveda, a diagnosis of Anapatya Vandhya with Artavakshaya and Karshya was made. Intervention: Therapeutic strategy included Shamana therapy for three months followed by Shodhana Therapy involving Uttarabasti (Intrauterine instillation of drug), Ksheerabasti and Nasya Karma. Outcome: Following treatment, 4 kg gain in body weight, moderate relief in acne and substantial improvement in duration and flow of menstruation was observed and the patient conceived in the 4th month of treatment course. Conclusion: This case report presents a successful outcome of Ayurveda regime planned on the basis of Ayurveda diagnosis in a rare case of Primary infertility associated with Lean PCOS